2000
DOI: 10.1007/s004149900088
|View full text |Cite
|
Sign up to set email alerts
|

Methamphetamine induces an increase in cell size and reorganization of myofibrils in cultured adult rat cardiomyocytes

Abstract: To investigate the direct effects of methamphetamine (MAP) on cardiac lesions seen in MAP abusers, isolated adult rat ventricular cardiomyocytes (ARCs) were exposed to MAP (0.05-1.0 mM) in medium 199 containing 10% fetal calf serum. Isolated ARCs attached to laminin-coated substrata and began to spread into polygonal shapes with pseudopodia at day 6 in normal culture. However, the cell attachment and spreading were inhibited by exposure to MAP (0.5 and 1.0 mM) for the first 7 days in culture. On the other hand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2001
2001
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 27 publications
(36 reference statements)
0
8
1
Order By: Relevance
“…In histopathological examinations, myocardial damage, such as eosinophilic changes, large and picnotic nuclei, hypertrophy and disarray of myofibers, was recognized in hearts from rats in the experimental group. These changes may arise from pharmacodynamic effects and/or direct toxicity of MAP (Matoba et al, 1985;He, 1995;He et al, 1996;Maeno et al, 2000). Although the MAP concentration (1.0 mg/kg) administered in our study was low (Cho, 1990;He et al, 1996), it was shown that MAP injured cardiomyocytes.…”
Section: Discussioncontrasting
confidence: 49%
“…In histopathological examinations, myocardial damage, such as eosinophilic changes, large and picnotic nuclei, hypertrophy and disarray of myofibers, was recognized in hearts from rats in the experimental group. These changes may arise from pharmacodynamic effects and/or direct toxicity of MAP (Matoba et al, 1985;He, 1995;He et al, 1996;Maeno et al, 2000). Although the MAP concentration (1.0 mg/kg) administered in our study was low (Cho, 1990;He et al, 1996), it was shown that MAP injured cardiomyocytes.…”
Section: Discussioncontrasting
confidence: 49%
“…After excision from male Wistar rat (7 wk old) under pentobarbital (50 mg/kg ip, Sigma, St Louis, MO) sedation, the heart was superfused with Krebs-Henseleit buffer solution composed of 118 mM NaCl, 2.6 mM KCl, 1.2 mM MgSO4, 1.2 mM KH2PO4, 11 mM glucose, and 25 mM NaHCO3 (pH 7.4), gassed with 95% O2 and 5% CO2. Cardiomyocytes were isolated by a collagenase digestion procedure described previously (13,20). Freshly isolated myocytes were suspended in Medium 199 (Sigma), containing 0.2% bovine serum albumin, and then seeded on laminin-coated glass coverslip bottom dishes and incubated at 37掳C until used.…”
Section: Methodsmentioning
confidence: 99%
“…However, since the effects of methamphetamine can include myocyte hypertrophy [10] and fibrosis [11,12], both relatively irreversible processes, it is likely that some patients will not recover left ventricular function with either appropriate medical therapy or abstinence from methamphetamine.…”
Section: Introductionmentioning
confidence: 99%